(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Premessa - 2. Il caso del Montenegro: identità nazionale e identità religiosa - 3. La costruzione di un’identità nazionale - 4. Prodromi di un divorzio annunciato - 5. Personalità giuridica delle Chiese e patrimonio religioso - 6. Beni culturali contesi - 7. Verso una risoluzione dei contrasti con la Chiesa ortodossa serba? - 8. Patrimonio culturale montenegrino e ruolo delle organizzazioni internazionali - 9. Conclusioni. Religious freedom, cultural heritage and identity: the case of Montenegro ABSTRACT: With the dissolution of the former Yugoslavia, the Balkan populations found themselves having to face the necessity of replacing their common Slavic origins with national identities that found a solid point of reference in religion. The cultural heritage, at first common thanks to Tito’s unifying work, became again the heritage of the single nationalities and the object of ethnic-local identity claims. In this situation, the anchorage to cultural heritage and the particular care taken by governments to claim its management and control, become instruments of identity whose effects inevitably reverberate on the delicate balance between the religious communities present in the different territories. The case of Montenegro shows the complicated relationship between the protection of cultural heritage, national identities and religious belonging to the different components of Orthodoxy, each of which claims exclusive and unique ownership over their respective territories, thus contributing to rewrite the contents of cultural heritage, reducing it to an increasingly local dimension. Thanks to the work of international organizations such as UNESCO with "its" world heritage and the Council of Europe, which is working to promote diversity and dialogue in the field of cultural heritage, this regains its dignity, respecting the citizens’ feelings and their quality of life.